2019
DOI: 10.1186/s12882-019-1294-1
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance among Malaysian patients with end-stage renal disease with pruritus

Abstract: BackgroundChronic kidney disease-associated pruritus (CKD-aP) is a well-recognized, frequent and compromising complication among patients on hemodialysis. Despite advancement in basic medical sciences, CKD-aP is still a major complication and a challenge for both physicians and patients to manage. The aim of this study was to estimate the prevalence of CKD-aP among hemodialysis patients in Malaysia, to determine the impact of CKD-aP on sleep quality and any factors associated with CKD-aP.MethodA multi-centered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 45 publications
0
19
0
2
Order By: Relevance
“…In a 2019 study published by Rehman et al, the prevalence of pruritus was 61.4%. 15 In a 2010 study by Martinez M. A. et al, the prevalence of half and half nails was 14.4%. 16 Also, in the study by Jamal A. in 2000, the prevalence of half and half nails in patients undergoing hemodialysis was 26%.…”
Section: Discussionmentioning
confidence: 95%
“…In a 2019 study published by Rehman et al, the prevalence of pruritus was 61.4%. 15 In a 2010 study by Martinez M. A. et al, the prevalence of half and half nails was 14.4%. 16 Also, in the study by Jamal A. in 2000, the prevalence of half and half nails in patients undergoing hemodialysis was 26%.…”
Section: Discussionmentioning
confidence: 95%
“…These results are higher than those found in previous research in patients receiving haemodialysis. Including fatigue (47%) [ 17 ], anxiety (17.5%) [ 18 ], depression (28%) [ 19 ] and sleep quality (48%) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these patients, 33.1% were prescribed a sleeping pill. A Malaysian study of 334 HD patients found a 5.47-fold increased risk of poor sleep quality in patients with moderate to severe pruritus compared with those with mild or no itch [ 43 ]. These findings are similarly noted in PD patients, with increased sleep disorders associated with increased severity of itch [ 14 ].…”
Section: Impact Of Ckd-ap On Health-related Qol (Hrqol) and Medical Outcomesmentioning
confidence: 99%